IMPLEMENTASI BLENDED LEARNING PADA KURIKULUM MERDEKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA OTOMOTIF SMK NEGERI 5 SURAKARTA - Sarman Sarman; Rasyid Sidik (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
The Mid Semester Score for the Fundamentals of the Automotive Engineering Program for students X TO_B for the odd semester of 2022/2023 is below the minimum mastery level. Students with scores below the minimum limit are 72.22%. Class Action Research is carried out to analyze student learning styles and present learning models that can improve student learning outcomes.The learning model presented in this study is blended learning. This research was conducted for 2 cycles, with a total of 4 face-to-face meetings. Each meeting has a focus on learning mechanical measuring instruments which are divided into caliper gauges, screw micrometers, dial indicators, and cylinder bore gauges. This research was attended by 34 students X TO_B Vocational High School 5 Surakarta in 2022/2023.The results of this study show that: 1) The blended learning model is effective in having a positive impact on increasing students' knowledge of X TO_B as evidenced by the results of the N-gain analysis; 2) The existence of innovative treatment in cycle 1 and cycle 2 learning related to optimizing the use of smartphone devices in learning, has proven to increase the effectiveness of learning by 3.24%; 3) The success of the blended learning model requires teacher control and student learning independence.